The Effect of Principal Leadership and Teacher Performance Toward Student Achievement - Mayasari, Intan; Arafat, Yasir; Setiawan, Andi Arif (Yayasan Sembilan Pemuda Indonesia, 2021)
This study determined the effect of principal leadership and teacher performance partially and simultaneously on student achievement. The research method is ex post facto with a total population of 53 teachers for the study sampling using total sampling so that the research sample is the same as the population, which is 53 respondents. Data collection techniques using documentation and questionnaires. The data analysis technique used the t-test and the f-test. The results of this study can be concluded that there is an influence of the principal's leadership and teacher performance partially and simultaneously on student achievement at Junior High School 02 Ogan Komering Ulu.